Doses, ambiente e forma de infecção causada por Fusarium solani f.sp. chrysanthemi em crisântemo (Dendranthema grandiflora) cv. calabria e seu controle por Trichoderma virens - Stefanelo, Daniela Rossato (2004)
Fusarium wilt has been damaging the chrysanthemum crop in the central region of Rio Grande do Sul, especially in those cultivated in greenhouse. Four experiments were done with the objective of studying the effect of doses, environment, and forms of infection of Fusarium solani f. sp. chrysanthemi in chrysanthemum and its control by Trichoderma virens. In the first experiment, the objective was to select the inoculum quantity of F. solani f. sp. chrysanthemi needed to infect chrysanthemum plants cv. Calabria and 6g/600 g of soil was found to be the most damaging to the plants. In the second experiment, the inoculation of the pathogen by soil infestation or root immersion, with and without physical damage of the roots, was tested. There was no difference between the inoculation forms and the plants with damaged roots showed less growth. In the third and fourth experiments six isolates and five doses of biological powders of Trichoderma virens were tested in the control of the Fusarium wilt and the growth of plants. Since the plants did not show symptoms of Fusarium, it was not possible to determine the best doses of Trichoderma to control the disease and the utilization of the biological powders interfered negatively in the growth of chrysanthemum plants cv. Calabria.